Subclavian Steal Syndrome Presented with Recurrent Syncope: A Case Report (Journal of National Institute of Neurosciences Bangladesh, 2024)
The Subclavian Steal Syndrome is a rare vascular disorder that results from the stenosis of the subclavian artery proximal to the origin of the vertebral artery. This obstruction causes the retrograde blood flow in the ipsilateral vertebral artery called “steal” because it steals blood from the cerebral circulation. We report a case of subclavian steal syndrome in a 57 yrs old male with HTN and CKD. The patient presented to the emergency department of a tertiary-level hospital with a one-week history of recurrent syncopal attack with an injury mark during his last episode. He had no known cardiac structural abnormality. Further clinical examination revealed absent radial and brachial pulse and non-recordable blood pressure in the left arm. Duplex study of the left upper limb arterial system showed left subclavian artery stenosis with the retrograde flow in the left vertebral artery (subclavian-vertebral steal). A coronary angiogram confirmed proximal stenosis of the subclavian artery. The condition was successfully treated with left subclavian stenting.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):161-167